The Effect Of Minimal Quantity Lubrication (MQL) On The Surface Roughness Of Titanium Alloy Ti-6Al-4V ELI In Turning Process - Che Haron, Che Hassan; A Ghani, Jaharah; Sulaiman, Mohd Amri; Lutfiah Intan; Kasim, Mohd Shahir (Trans Tech Publication, Switzerland, 2011)
This paper investigates the effect of minimum quantity lubricant (MQL) on the surface roughness of titanium alloy Ti-6Al-4V ELI when turning using uncoated tungsten carbide tool. The response surface method (RSM) design of experiment using Box-behnken was used to accomodate the turning experiment factors and levels. Turning parameters studied were cutting speed (100, 135, 170 m/min), feed rate (0.15, 0.2, 0.25 mm/rev) and depth of cut (0.6, 0.8, 1.0 mm). The results show that the feed rate was the most influence factor controlling the surface roughness produced. The feed rate (F) was found directly proportional with the surface roughness value (Ra) but inversely proportional to the cutting speed (Vc). MINITAB software was used to develop a surface roughness model, and the optimum condition was at 160 m/min of cutting speed, 0.18 mm/rev of feed rate and 1 mm of depth of cut. At the optimum condition low value of 1.54 µm surface roughness was obtained.